Approximation through suffixation: -ḍḍu/-a in Sicilian - Luisa Brucale; Egle Mocciaro (Zeitschrift für Wortbildung)
This article investigates the use of the Sicilian suffix -ḍḍu/-a for the expression of approximation. On the basis of a survey of a corpus of ethnotexts and the outputs of a translation questionnaire, we propose that approximation is a core value in the semantic network of the suffix, expressing a certain distance from the default values conveyed by the base. In terms of prototypicality, this distance may occur from the categorial centre (internal approximation): the suffix modifies the semantics of the base but does not alter the categorial status of the referent. Alternatively, the suffix may impact on categorial membership tout court (external approximation), questioning the categorial properties of the base. Based on this classification, the semantic cores of the suffix are represented in a map showing the connections between the various meanings identified in the corpus.